Contrasting Trends of Smoking Cessation Status: Insights From the Stages of Change Theory Using Repeat Data From the Global Adult Tobacco Survey, Thailand (2009 and 2011) and Turkey (2008 and 2012) - Mbulo, Lazarous (Prev Chronic Dis, 2017)
OBJECTIVE: The World Health Organization recommends that smokers be offered help to quit. A better understanding of smokers’ interest in and commitment to quitting could guide tobacco control efforts. We assessed temporal differences in stages of change toward quitting among smokers in Thailand and Turkey. METHODS: Two waves (independent samples) of data from the Global Adult Tobacco Survey, a national household survey of adults aged 15 years or older, were assessed for Thailand (2009 and 2011) and Turkey (2008 and 2012). Current smokers were categorized into 3 stages of change based on their cessation status: precontemplation, contemplation, and preparation. Relative change in the proportion of smokers in each stage between waves 1 and 2 was computed for each country. RESULTS: Between waves, overall current tobacco smoking did not change in Thailand (23.7% to 24.0%) but declined in Turkey (31.2% to 27.1%; P < .001). Between 2009 and 2011, precontemplation increased among smokers in Thailand (76.1% to 85.4%; P < .001), whereas contemplation (17.6% to 12.0%; P < .001) and preparation (6.3% to 2.6%; P < .001) declined. Between 2008 and 2012, there were declines in precontemplation among smokers in Turkey (72.2% to 64.6%; P < .001), whereas there were increases in contemplation (21.2% to 26.9%; P = .008) and no significant change in preparation (6.5% to 8.5%; P = .097). CONCLUSION: Nearly two-thirds of smokers in Turkey and more than two-thirds in Thailand were in the precontemplation stage during the last survey wave assessed. The proportion of smokers in the preparation stage increased in Turkey but declined in Thailand. Identifying stages of cessation helps guide population-based targeted interventions to support smokers at varying stages of change toward quitting.